EARNINGS STATEMENTS IN PERIODS OF PROSPERITY AND DEPRESSION. - Reighard, John J. (The Accounting Review, 1932)
Accounting statements are one of the chief sources of data which mold the financial activity over the various phases of the business cycle. They are the basis on which capital funds are (or should be) invested and earnings distributed. Thus they contribute directly to those influences which bring about business inflation, and, in turn, they measure the extent of the aftermath of recession, possibly viewing it through the dark-colored spectacles of pessimism. This paper is an attempt to indicate some considerations with which accounting is concerned in its relation to the business cycle. The paper has been suggested by the types of financing which have taken place in the recent period of prosperity, by the several questions raised in accounting theory by the fact or myth of appreciation, that there is a fundamental error in bookkeeping which tends to augment directly those influences that contribute to the optimism of business expansion and the pessimism of depression. The discussion will be limited to a consideration of accounting for income over the period of the business cycle.